2020
DOI: 10.3390/pharmaceutics12060529
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Extracellular Vesicles/Exosomes as a New Tool against Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are commonly generated by intracellular accumulation of misfolded/aggregated mutated proteins. These abnormal protein aggregates impair the functions of mitochondria and induce oxidative stress, thereby resulting in neuronal cell death. In turn, neuronal damage induces chronic inflammation and neurodegeneration. Thus, reducing/eliminating these abnormal protein aggregates is a priority for any anti-neurodegenerative therapeutic approach. Although several antibodies against mutated ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…Through the study of the exosome sorting mechanisms, nucleic acids and proteins enrichment on engineered exosomes may be used target exosomes to specific cell types and achieve the high-concentration impact targeted therapy. However, the application of exosomes is difficult because of a number of unresolved issues, such as the efficiency of exosome engineering, cost-effectiveness, safety, and biodistribution/pharmacokinetics 184 .…”
Section: Exosome-based Strategies For Diagnosis and Therapymentioning
confidence: 99%
“…Through the study of the exosome sorting mechanisms, nucleic acids and proteins enrichment on engineered exosomes may be used target exosomes to specific cell types and achieve the high-concentration impact targeted therapy. However, the application of exosomes is difficult because of a number of unresolved issues, such as the efficiency of exosome engineering, cost-effectiveness, safety, and biodistribution/pharmacokinetics 184 .…”
Section: Exosome-based Strategies For Diagnosis and Therapymentioning
confidence: 99%
“…At least two conditions should be met while engineering exosomes for brain targeting: (I) BioEng-Exo must not interact with the physiological barriers, which could limit their diffusion except the plasma membrane of the target cell, and (II) exosomes should be engineered to preferably target cell types relevant to disease pathogenesis, e.g., rabies virus glycoprotein (RVG) is used to engineer exosomes specifically for CNS disease. RVG is a 29-amino-acid peptide that specifically binds to neural cells’ nicotinic acetylcholine receptor ( Ferrantelli et al, 2020 ). T7 peptides, that target the cellular transferrin receptor in the brain has been successfully used for targeting glioblastoma in the brain ( Kim G. et al, 2020 ).…”
Section: Bioengineering Of Exosomes For Brain Targetingmentioning
confidence: 99%
“…The use of EVs is currently being evaluated as a therapeutic strategy for treatment of variety of diseases including cancers (Pirisinu et al., 2020; Walker et al., 2019), cardiovascular diseases (De Abreu et al., 2020), neurogenerative diseases (Ferrantelli et al., 2020) and diabetes (Noren Hooten & Evans, 2020; Xiao et al., 2019). Many of these pre‐clinical studies have shown promise in in vivo models and use EVs to deliver specific cargo such as miRNAs, siRNAs and proteins.…”
Section: Why Are Evs Advantageous As Therapeutics?mentioning
confidence: 99%
“…Additionally, EVs are ‘targetable’. Display of specific proteins, and possibly other biomolecules, allows EVs to be sorted to certain cell types and tissues or away from undesired recipients (Ferrantelli, Chiozzini, Leone, Manfredi, & Federico, 2020; Pirisinu et al., 2020; Walker et al., 2019). EV engineering, by manipulating the EV source or by altering EVs post‐production, can be used to enhance such targeting.…”
Section: Introductionmentioning
confidence: 99%